2017
DOI: 10.1098/rspb.2017.1836
|View full text |Cite
|
Sign up to set email alerts
|

Reply to comment by Kienle et al . 2017

Abstract: Kienle et al. [1] suggest amendments to our framework for feeding in predatory aquatic mammals [2]. Below we reply to their suggestions and demonstrate that they are fundamentally flawed from both a mechanical (feeding cycle, strategies) and an evolutionary perspective. They do, however, inspire an important addition to the range and structuring of capture behaviours encoded in our framework.Feeding cycle. Our framework groups feeding behaviours with similar functions, such as capture and processing, and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Whales appear in the fossil record approximately 52.5 million years ago (Mya), with the two extant cetacean suborders, mysticetes (baleen whales) and odontocetes (toothed whales), diverging around 39 million years ago (Mya) [ 3 ]. Mysticetes evolved large body sizes and specialisations for bulk filter feeding whilst odontocetes evolved echolocation (biosonar) [ 4 6 ] and employ various raptorial and/or suction feeding strategies [ 7 , 8 ]. Cetaceans have undergone extensive morphological changes to adapt to a fully aquatic lifestyle [ 9 , 10 ] and show extremely divergent morphologies compared to their terrestrial artiodactyl relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Whales appear in the fossil record approximately 52.5 million years ago (Mya), with the two extant cetacean suborders, mysticetes (baleen whales) and odontocetes (toothed whales), diverging around 39 million years ago (Mya) [ 3 ]. Mysticetes evolved large body sizes and specialisations for bulk filter feeding whilst odontocetes evolved echolocation (biosonar) [ 4 6 ] and employ various raptorial and/or suction feeding strategies [ 7 , 8 ]. Cetaceans have undergone extensive morphological changes to adapt to a fully aquatic lifestyle [ 9 , 10 ] and show extremely divergent morphologies compared to their terrestrial artiodactyl relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hocking et al (2017b) also challenged the capacity of dental filter feeding in Coronodon, proposed by Geisler et al (2017), suggesting in contrast a mix of raptorial and suction feeding in the latter; they also concluded that suction feeding may have preceded the emergence of baleen. Therefore, both the evolutionary history and the feeding ecology of early mysticetes currently remain unclear and a matter of debate (Kienle et al 2017;Hocking et al 2017c).…”
Section: Introductionmentioning
confidence: 99%
“…This is made possible by their relatively primitive forelimb morphology, including flexible digits and strong claws. Semi-aquatic feeding behaviours, where prey is captured underwater before being brought to the surface for processing, were likely important when pinnipeds first began the transition from feeding on land to feeding in water [ 5 , 6 ]. Unlike more specialized aquatic feeding strategies common in living pinnipeds (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, all of this is further complicated by the need to dramatically modify their body form to increase streamlining and to adapt their limbs for generating propulsion when swimming [ 4 ]. In response to these challenges, marine mammals have adopted a myriad of aquatic feeding strategies, involving behaviours which are often so highly specialized that they would be impossible to use on land [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation